2007
DOI: 10.14411/fp.2007.022
|View full text |Cite
|
Sign up to set email alerts
|

The first finding of myxosporean development from plasmodia to spores in terrestrial mammals: Soricimyxum fegati gen. et sp. n. (Myxozoa) from Sorex araneus (Soricomorpha)

Abstract: Abstract. Soricimyxum fegati gen. et sp. n. is a new myxosporean (Myxozoa) species discovered in the liver of shrews, Sorex araneus L., collected in the Bialowieza primeval forest (Poland). Both developmental stages and mature spores were found during a histological study. The infection had about 40% prevalence at the investigated locality. Plasmodia were polysporic. Elongated plasmodia with an average size of 30 by 8 µm occupied bile ducts and larger rounded plasmodia up to 80 µm in diameter were found in liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 18 publications
3
20
0
4
Order By: Relevance
“…Morphologically, myxospores from the two shrew species appeared identical and matched previous reports of S. fegati (Dyková et al 2007, Prunescu et al 2007). We observed that spores from both hosts had two to three polar filament turns within the polar capsules, whereas S. fegati is reported to have one to two turns.…”
Section: Soricimyxum Minuti Sp Nsupporting
confidence: 88%
See 3 more Smart Citations
“…Morphologically, myxospores from the two shrew species appeared identical and matched previous reports of S. fegati (Dyková et al 2007, Prunescu et al 2007). We observed that spores from both hosts had two to three polar filament turns within the polar capsules, whereas S. fegati is reported to have one to two turns.…”
Section: Soricimyxum Minuti Sp Nsupporting
confidence: 88%
“…We observed that spores from both hosts had two to three polar filament turns within the polar capsules, whereas S. fegati is reported to have one to two turns. Morphometrically, spores found in both shrew species were inseparable in all dimensions, and equivalent to measurements of S. fegati made by Dyková et al (2007) who showed, by re-measurement of the type material, that the type spore dimensions (Prunescu et al 2007) were erroneously small. The similarity in measurements between S. fegati and S. minuti sp.…”
Section: Soricimyxum Minuti Sp Nsupporting
confidence: 79%
See 2 more Smart Citations
“…However, three more genera (Soricimyxum, Gadimyxa, Thelohanelloid) with type species S. fegati Prunescu et al 2007 from liver of Sorex araneus; G. atlantica Koie et al 2007 from urinary system of Gadus morhua and T. bengalensis Sarkar 2009 from gall bladder of Arius sagor have been described subsequently. Phylum Myxozoa has been studied by only limited number of workers in Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%